2018
DOI: 10.1038/s41467-018-03576-3
|View full text |Cite
|
Sign up to set email alerts
|

The MerR-like protein BldC binds DNA direct repeats as cooperative multimers to regulate Streptomyces development

Abstract: Streptomycetes are notable for their complex life cycle and production of most clinically important antibiotics. A key factor that controls entry into development and the onset of antibiotic production is the 68-residue protein, BldC. BldC is a putative DNA-binding protein related to MerR regulators, but lacks coiled-coil dimerization and effector-binding domains characteristic of classical MerR proteins. Hence, the molecular function of the protein has been unclear. Here we show that BldC is indeed a DNA-bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 49 publications
2
35
0
Order By: Relevance
“…MtrA acts as both activator and repressor in other actinomycetes, but how it impacts bld and whi gene expression remains to be addressed in S. venezuelae . Another example is the MerR-like regulator, BldC, which binds to a number of promoters that are also direct targets of BldD; like MtrA, BldC can have both repressor and activator functions (25).…”
Section: Resultsmentioning
confidence: 99%
“…MtrA acts as both activator and repressor in other actinomycetes, but how it impacts bld and whi gene expression remains to be addressed in S. venezuelae . Another example is the MerR-like regulator, BldC, which binds to a number of promoters that are also direct targets of BldD; like MtrA, BldC can have both repressor and activator functions (25).…”
Section: Resultsmentioning
confidence: 99%
“…5 and Table 1). Schumacher et al (11) characterized the interaction of S. coelicolor BldC with the promoters of two of its previously known targets, whiI and the smeA-ssfA operon. whiI encodes an orphan response regulator that is essential for the later stages of sporulation, when it forms a functional heterodimer with a second orphan response regulator, BldM, enabling WhiI to bind to DNA and regulate the expression of ~40 sporulation genes (14).…”
Section: Resultsmentioning
confidence: 99%
“…Schumacher et al (11) showed that BldC binds to DNA in a head-to-tail fashion at a variable number of direct repeats. So, for example, in the whiI- BldC structure, there are two direct repeats resulting in the head-to-tail oligomerisation of two BldC monomers, whereas in the smeA- BldC structure there are four direct repeats resulting in the head-to-tail oligomerisation of four BldC monomers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations